Crosstalk Between the Gut Microbiome and Bioactive Lipids: Therapeutic Targets in Cognitive Frailty - Baptista, Liliana C.; Sun, Yi; Carter, Christy S.; Buford, Thomas W. (Frontiers in Nutrition, 2020)
Cognitive frailty is a geriatric condition defined by the coexistence of cognitive impairment and physical frailty. This “composite” aging phenotype is associated with a higher risk of several adverse health-related outcomes including dementia. In the last decade, cognitive frailty has gained more attention from the scientific community that has focused on understanding the clinical impact, physiological and pathological mechanisms of development, and in identifying preventive and/or rehabilitative therapeutic interventions. The ascension of microbiota in neural signaling increased the interest in targeting the gut-brain axis as a modulation strategy. Multiple studies on gastroenteric, metabolic and neurodegenerative diseases support the existence of a wide bidirectional communication network of signaling mediators, e.g. bioactive lipids, that can modulate inflammation, gut permeability, microbiota composition and the gut-brain axis. This crosstalk between the gut- brain axis, microbiome and bioactive lipids may emerge as a promising therapeutic strategy to counteract cognitive frailty. In this review, we summarize the evidence in the literature regarding the link between gut microbiome, brain and several families of bioactive lipids. In addition, we also explore the applicability of several bioactive lipid members as a potential route for therapeutic interventions to combat cognitive frailty.